Effects of dietary supplementation with abscisic acid on Apis mellifera colonies confined in overwintering nucleus: studies on the adult honey bee population, nosemosis, and expression of nutrition- and immune-related genes - Nicolas Szawarski; Lorenzo Lamattina; Martin Javier Eguaras; Facundo Ramos; Giulia Mitton; Eugenia Olivera; Facundo Meroi Arcerito; Constanza Brasesco; Gregorio De Landa; Silvina Quintana; Enzo Dominguez; Matías Daniel Maggi (EUNK Revista Científica de Abejas y Apicultores)
Due to the complex interactions between pathogens and environmental and anthropogenic stressors, in temperate climates, honey bee populations suffer depopulation and/or colony death, mainly during overwintering. Nosema spp. comprises one of the primary pathogens affecting Apis mellifera colonies, and cold ambient temperature promotes its intensity in worker bees. Additionally, the drastic reduction of plants decreases the diversity and quality of pollen and nectar diet for bees, leading to malnutrition of honey bee colonies and compromising the immunity of individuals, increasingly vulnerable to parasites and pathogens. Previous studies showed that abscisic acid (ABA) stimulates the health of honey bees at individual and colony levels against different stress conditions. This study aimed at evaluating the effect of supplementing the diet with ABA on overwintering nuclei, considering the population growth of honey bee colonies, nosemosis dynamics, and the nutrition- and immune-related gene expression of honey bees. Results in this work showed that ABA had no significant effect on any of the parameters studied. However, taking into account the results observed in the variables measured, we encourage the development of more studies focused on this topic, using more colonies per group and measuring the blooming period and the plant species involved.